Lifestyle entrepreneurs, hostels and backpacker tourism development: the case of San Cristóbal de las Casas, Mexico - Brenner, Ludger; Fricke, Jörn (El Periplo Sustentable; Núm. 31 (2016): Número Treinta y uno, 2016)
Drawing on the analytical framework of lifestyle entrepreneurs, this paper analyzes their motivation, objectives and business strategies in relation to the management of "hostels" in an effort to shed light on key agents of (scarcely investigated) backpacker-driven tourism development at San Cristóbal de las Casas. Based on in-depth interviews with owners and managers, we conclude that lifestyle entrepreneurs strive to meet the demands of contemporary backpackers by providing a specific ambience and outpacing more profit-oriented competitors. In addition, business owners work to sustain an explicitly hedonistic way of life to perpetuate their status as “senior” backpackers who offer customized, hard-to-imitate services. However, lifestyle entrepreneurs have also developed strategies to cope with increasing competition and recent demand-related trends.